An Unusual Case Report of Genital Elephantiasis Nostras Verrucosa - Tantivithiwate, Thamonwan; Thanomkitti, Kanchalit; Pattanaprichakul, Penvadee (Thai Journal of Dermatology, 2023)
Elephantiasis nostras verrucosa is an unusual cutaneous manifestation of chronic nonfilarial lymphedema. It features warty, leathery, or verrucous hyperkeratotic plaques with a cobblestone appearance on nonpitting edematous skin. This condition predominantly affects the lower extremities. Herein, we present a case of elephantiasis nostras verrucosa with an uncommon presentation in the genitalia, accompanied by a superficial fungal infection.